Smart and Sustainable Engineering for Next Generation Applications Proceeding of the Second International Conference on Emerging Trends in Electrical, Electronic and Communications Engineering (ELECOM 2018), November 28-30, 2018, Mauritius - Fleming, Peter; Lacquet, Beatrys Margaretha; Sanei, Saeid; Deb, Kalyanmoy; Jakobsson, Andreas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book reports on advanced theories and methods in two related engineering fields: electrical and electronic engineering, and communications engineering and computing. It highlights areas of global and growing importance, such as renewable energy, power systems, mobile communications, security and the Internet of Things (IoT). The contributions cover a number of current research issues, including smart grids, photovoltaic systems, wireless power transfer, signal processing, 4G and 5G technologies, IoT applications, mobile cloud computing and many more. Based on the proceedings of the Second International Conference on Emerging Trends in Electrical, Electronic and Communications Engineering (ELECOM 2018), held in Mauritius from November 20 to 30, 2018, the book provides graduate students, researchers and professionals with a snapshot of the state-of-the-art and a source of new ideas for future research and collaborations.
Hand Gesture Controller for Robotic-Wheelchair Using Microelectromechanical Sensor ADXL -- A Jaya-based Invasive Weed Optimization Technique for Load Frequency Control -- A Hybrid Optimisation Algorithm for Voltage Control -- Optimization of Load Frequency Control for Non-Linear System -- Efficiency of VFD coupled Induction Motors Operating in the Scalar Mode with Different Types of Loads.
Keywords: Telecommunication; Application software; Electric power production; Communications Engineering, Networks; Computer and Information Systems Applications; Electrical Power Engineering; Mechanical Power Engineering